2014
DOI: 10.1001/jama.2013.285141
|View full text |Cite
|
Sign up to set email alerts
|

Risk of End-Stage Renal Disease Following Live Kidney Donation

Abstract: Risk of end-stage renal disease (ESRD) in kidney donors has been compared with risk faced by the general population, but the general population represents an unscreened, high-risk comparator. A comparison to similarly screened healthy nondonors would more properly estimate the sequelae of kidney donation.OBJECTIVES To compare the risk of ESRD in kidney donors with that of a healthy cohort of nondonors who are at equally low risk of renal disease and free of contraindications to live donation and to stratify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
675
1
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 844 publications
(709 citation statements)
references
References 28 publications
16
675
1
17
Order By: Relevance
“…A recent report of 103 African-American donors at two centers suggested that the frequency of post-donation hypertension may exceed that of matched controls, noting a high proportion of previously undiagnosed hypertension identified through study encounters [12]. Further, a new study of data for 96,217 US living donors identified a small but significant increase in ESRD risk attributable to donation that was highest in African-Americans [13], illustrating the need to understand mediators of disparities in post-donation ESRD. Management of hypertension may include lifestyle modification and close observation, followed by pharmacologic therapy with antihypertensive medications (AHM) in patients who do not achieve treatment goals [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report of 103 African-American donors at two centers suggested that the frequency of post-donation hypertension may exceed that of matched controls, noting a high proportion of previously undiagnosed hypertension identified through study encounters [12]. Further, a new study of data for 96,217 US living donors identified a small but significant increase in ESRD risk attributable to donation that was highest in African-Americans [13], illustrating the need to understand mediators of disparities in post-donation ESRD. Management of hypertension may include lifestyle modification and close observation, followed by pharmacologic therapy with antihypertensive medications (AHM) in patients who do not achieve treatment goals [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ESRD is a life-threatening condition [4]. In young and healthy persons, the estimated risk of ESRD at 15 yr is 0.04% (95% CI, 0.008-0.09), reaching a peak of 0.3% (95% CI, 0.2-0.4) in healthy kidney donors [5]. Due to older age, high prevalence of associated comorbidities, and reduced number of nephrons, ESRD risk after surgery for renal cancer is significantly more common.…”
mentioning
confidence: 99%
“…Muzzale et al wrote that although there is an increased risk of ESRD in renal donors, the magnitude of absolute risk increase was very small, thus supporting our conclusion as well. [15] Future directions for this clinically and ethically important question would be with three dimensional radiological measurement of pre and post-operative renal volume and the usage of GFR with age, ethnicity and BMI factored in to investigate the relationship between residual renal volume and renal function in the renal donor. We eagerly await future research on this topic for validation of our findings.…”
Section: Resultsmentioning
confidence: 99%